Determination of etomidate and etomidate acid in hair using liquid chromatography–tandem mass spectrometry - Park, Young J.; Cho, Eunsu; Kim, So H.; Lee, Heesang; Jegal, Hyeon; Park, Meejung; Choe, Sanggil; Sim, Yeong E.; Baek, Seung Hoon; Kim, Kang M.; Pyo, Jaesung (Journal of Forensic Sciences, 2022)
Etomidate, with efficacy similar to that of propofol, has been used as a propofol substitute because propofol is a designated narcotic drug, and an increase in the frequency of illegal distribution and misuse has been reported in Korea. Previous analytical studies on etomidate used blood and urine. For long-term use and timing estimation, a method for etomidate analysis using hair should be developed. Therefore, in this study, an analytical method using LC–MS/MS was developed to determine etomidate and its major metabolite in hair. Human hair samples were segmented after washing to eliminate possible contaminants on the hair and stirred with methanol. The LC–MS/MS conditions were optimized, and the chromatographic separation time was 10 min. Selectivity, linearity, limit of detection, limit of quantification, precision, accuracy, recovery, process efficiency, matrix effect, and stability were evaluated to validate the analytical method. The calibration curves ranged from 0.25 to 50 pg/mg for etomidate and 2–250 pg/mg for etomidate acid; the coefficients of determination were higher than 0.997. The intra- and inter-assay precision results for all the compounds were <15% and satisfied at recovery, process efficiency, matrix effect, and stability. In addition, this method was applied to the hair of 4 rats which are administered with etomidate to evaluate. The etomidate concentrations in the rat hair ranged from 2.60 to 8.50 pg/mg, and the etomidate acid concentrations were 2.06–7.13 pg/mg. Thus, this method can be used as basic data for monitoring etomidate in hair.
Keywords: Animals; Chromatography, Liquid; Etomidate; Hair; Humans; Propofol; Rats; Substance Abuse Detection; Tandem Mass Spectrometry; etomidate; etomidate acid; forensic toxicology; hair analysis; LC–MS/MS; method validation